Giant mucinous cystadenoma of ovary in an adolescent girl: a case report - Singh, Gaurav; Narain, Anupriya; Dhawan, Shashi; Kulshrestha, Rajeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian masses are rarer in children and adolescent than adults. Simple ovarian cysts are most common non-neoplastic masses in children. We report this case to emphasize that mass abdomen in adolescents can be missed being asymptomatic. A 16-year-old girl presented intermittent pain abdomen, nausea and decreased appetite for 3 months. Her menstrual cycles were normal and regular. Tumor markers were within normal limits. Exploratory laparotomy with decompression of cyst followed by cystectomy was done. The histopathology revealed the mass to be a mucinous cystadenoma. Post op course was smooth. The patients’ age, size of the cyst and menopausal status of the patient are the important deciding factor in the plan of management. A conservative surgical procedure should be the primary aim in order to preserve patient’s fertility.